1994
DOI: 10.1021/bi00198a027
|View full text |Cite
|
Sign up to set email alerts
|

Melting and Premelting Transitions of an Oligomer Measured by DNA Base Fluorescence and Absorption

Abstract: Incorporation of 2-aminopurine (2AP) in place of adenine gives an optical probe of local and global DNA conformation. The temperature dependence of the absorption of the duplex d[CTGA(2AP)-TTCAG]2 DNA decamer shows that the helix has approximately an all-or-none melting transition. Absorbance at wavelengths of 260 and 330 nm monitors the average normal base conformation and the 2AP base local conformation, respectively. From this measure, the 2AP base melts less than 1 degree C below the other bases. Temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
140
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 33 publications
12
140
1
Order By: Relevance
“…The melting profiles from these two sets of measurements overlap for each of the four 2AP-substituted analogs, indicating an all-or-none melting process. The melting profiles obtained from changes in the fluorescence of 2AP are, however, shifted to lower temperatures, suggesting a premelted state in which the bases are mobile while maintaining a time-averaged helical structure (21).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The melting profiles from these two sets of measurements overlap for each of the four 2AP-substituted analogs, indicating an all-or-none melting process. The melting profiles obtained from changes in the fluorescence of 2AP are, however, shifted to lower temperatures, suggesting a premelted state in which the bases are mobile while maintaining a time-averaged helical structure (21).…”
Section: Resultsmentioning
confidence: 94%
“…1). The fluorescence of 2AP decreases by about a factor of 2 when the base is hydrogenbonded and stacked compared with the single-stranded state and provides both a local and a global probe for hairpin melting (20)(21)(22). Equilibrium melting profiles that monitor the average fraction of broken bonds (absorbance at 266 nm) as well as the fraction of broken bonds at the 2AP substituted site (absorbance at 330 nm) were monitored (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of the structure and stability of Ap-containing DNA duplexes by NMR, fluorescence, and calorimetry have shown that Ap undergoes normal Watson-Crick pairing with T and is well stacked within the DNA helix in a manner that is similar to adenine (37)(38)(39)(40). The guanine analog, I, is base-paired with C. DNA duplexes substituted with I are not identical to their G-containing counterparts as the exchange of G for I results in the loss of the exocyclic amino group in the minor groove and the loss of one H bond in the base pair with C. However, the structural consequences of a single I substitution are relatively minor, based on crystal structures (41,42) and theoretical investigations (43).…”
Section: Resultsmentioning
confidence: 99%
“…Many such investigations rely on the notion that base stacking is solely responsible for quenching Ap* fluorescence. Yet, various mechanisms and͞or conditions, including stacking (39,48), hydrogen bonding (34,38), base-base collisions (48), and CT reactions (6,7,32) have been proposed to explain the quenching of Ap* fluorescence in DNA. Furthermore, the dynamic exchange of Ap between conformational states in DNA modulates stacking, H bonding, and other base-base interactions and reactions on the fluorescence time scale, and thereby regulates all quenching reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Upon phosphodiester cleavage, the base stacking, solvation, and dynamics of 2AP are likely to change substantially. 22 Since the photophysical properties of 2AP are known to change in response to changes in its local environment, 23À26 it is expected that continuous fluorescence measurements can be used to monitor the progress of ribozyme-mediated cleavage in real time. 27 …”
Section: Designmentioning
confidence: 99%